Green human resource management in the era of digitalization: Hospitality sector - Vi, Nguyen Lam Ngoc; Cup, Le Van (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
In the precipice of the digital age, organizations are navigating through a transformation that is not only technological but also ecological. In light of the increasing emphasis on sustainability within the business sector, Green Human Resource Management (Green HRM) has surfaced as a crucial approach that incorporates environmental stewardship into fundamental human resource operations. The convergence of digitalization and Green HRM signifies an unprecedented paradigm shift, presenting a chance to reconceptualize the function of human resources in promoting environmentally conscious business strategies. This study investigates the incorporation of Green HRM into the digital age in the hospitality sector with 252 respondents including staffs and managers, examining how digital platforms and tools can facilitate the implementation of environmentally sustainable human resource practices.